Pengaruh Work life balance, Burnout, dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Tenaga Kependidikan di Universitas IGM - Meyvira Permata; Zunaidah, Zunaidah; Hadri, Muhammad Ichsan (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of work-life balance, burnout, and non-physical work environment on job satisfaction among educational staff at Indo Global Mandiri University (UIGM). Using a quantitative approach, the results show that work-life balance has a positive and significant effect on job satisfaction, while burnout negatively and significantly affects it. Additionally, the non-physical work environment shows a positive and significant influence on job satisfaction. These findings highlight the importance of organizational support in achieving optimal job satisfaction through improved work-life balance and work environment, while addressing burnout among educational personnel.